Pandion haliaëtus (Accipitridae) - Beutefang - Rüppell, Georg; Möller, Wilhelm (IWF (Göttingen), 1981)
Fischadler (Freilandaufnahmen). Suchflug, Flugmanöver zum Beutestoß, abgebrochene Stöße, Eintauchen, Kampf mit der Beute, Fischtransport. Mit Zeitdehnung. : Osprey (open air shots). Searching flight, flight manoeuvres preparatory to diving, breaking out of a dive, entering the water, struggles with a fish, and transporting a fish are shown. With slow-motion.